(untitled) (Medico Legal Update, 2020)
The national TB Program according to the long-term plan is to prevent and control of drug resistance through Management Program of MDR-TB. The objective of the program are reducing morbidity, mortality and transmission of MDR-TB. Medan is an area with the highest case of MDR-TB in Sumatera Utara Province. Until November 2018 MDR-TB case has been confirmed in the city of Medan as many as 324, which has not started the treatment are 61 patients (19%). This research using case-control design and population is all people with MDR-TB in Medan city that recorded in E-TB Manager data. Sample case is the confirmed MDR-TB person who has not started the treatment as many as 13 people while the control is a confirmed person MDR-TB and willing to start the treatment as many as 31 people. The data is collected through interview using questionnaires and has received approval from the Ethics committee of the Faculty of Nursing University of Sumatera Utara. The data analysis is conducted with the chi-square test and the OR calculation to assess which variables affect the action of beginning MDR-TB treatment. Results showed that there was no influence of the distance of health facilities (p = 0.188) and family number at home (p = 0.507) with the status of starting treatment MDR-TB. There was influence of historical of TB with the status of starting treatment respondent MDR-TB (p = 0.021)